Geometry Worksheet Based on Augmented Reality to Improve Slow Learner Student's Visual-Spatial Ability - Qhorisa, Agnes; Andriyani, Andriyani; Bonaya, Halkano Qalla (International Journal on Emerging Mathematics Education, 2025)
The purpose of this study to develop geometry worksheet to improve the visual-spatial abilities of slow-learner students. This study uses the method is Research and Development (R&D) research which in the development process uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects in this study were students in the inclusion class of one of the Muhammadiyah high schools in the city of Yogyakarta. Data collection methods are observation, interviews, pretest-posttest tests, and questionnaires. The instruments used in this study were questionnaire instrument validated by media experts and material experts, an instrument for student responses, and pretest-posttest questions. Based on the validity test, the worksheet is included in the good category in terms of material with an average score of 79.67, and very good in terms of media with an average score of 77 so it is valid. Then, based on student responses, the worksheet is included in the good category with an average score of 78 so it is practical. Meanwhile, based on the results of the pretest-posttest achievements there was an increase, so it is included in the effective category to improve students' visual-spatial abilities.